(untitled) (American Journal of Islam and Society, 2000)
This article describes the evolution of Indonesia’s voluntary sector and the role of nongovernmental and private voluntary organizations in the development of Indonesia’s civil society. The paper describes how NGOs and PYOs complement and supplement the role of government in the social and economic development of the society. It also discusses how these organizations manage their responsibility in challenging the government while often remaining financially dependent on the government for their existence. The paper also advances discussions about the organizational theory of voluntary organizations and their particular development in Indonesia.